METHOD AND APPARATUS FOR RESONANT POWER CONVERSION - ZIMMANCK, DONALD RICHARD; FORNAGE, MARTIN (2012)
A method and apparatus for providing multi-phase power. In one embodiment, the apparatus comprises a cycloconverter controller for determining a charge ratio based on a reference waveform; and a cycloconverter, coupled to the cycloconverter controller and to a multi-phase AC line, for selectively coupling an alternating current to each line of the multi-phase AC line based on the charge ratio.